Development and validation of environmental friendly method for determination of heavy metals in pastures - Chaparro G., Amanda Lucia; García F., Jhon Jairo; Cardona R., Yaneth; Bustamante C., Jhon Jairo; Peláez P., Manuel (Revista de Ciencias Agrícolas, 2016)
Heavy metals are dangerous for living beings and environment, because they cannot be degraded or destroyed. They can reach human beings through the food chain; therefore, their determination in different matrices for human and animal consumption is very important. The method currently used for their extraction is by ash, which entails long processing times and high energy consumption. For this reason, in this study, an environmental friendly method, for digestion and extraction Cd+2 and Pb+2, in pastures, was developed and validated; using ultrasound and atomic absorption spectroscopy. Different variables that affect the digestion were evaluated, such as position on the ultrasound, sample weight, solvent, solvent volume, sonication time and type of container, in samples of pastures doped with metals, using recovery rate as a response variable. The conditions for digestion and extraction of Cd+2 an Pb+2 were: 0.50g of grass in 3.00mL of aqua regia (HCl:HNO3-3:1) exposed for 60min to ultrasound in conical glass tubes. The proposed procedure showed a linear behavior in the range of 0.50 to 8.00 mg/Kg, with 0.9968 and 0.9999 of R2 for Cd+2 and P+2b respectively. The limits of detection and quantification were 0.25 - 0.43 mg/Kg for Cd+2 and 0.22 - 0.37 mg/Kg for Pb+2. The proposed methodology was compared with the conventional technique, and this method allowed determining trace levels of these toxic metals in a forage sample from Magdalena region, with recoveries of 97.54% and 98.62%, respectively.